2016
DOI: 10.1186/s12891-016-0995-x
|View full text |Cite
|
Sign up to set email alerts
|

The protective role of autophagy in experimental osteoarthritis, and the therapeutic effects of Torin 1 on osteoarthritis by activating autophagy

Abstract: BackgroundRecent studies have shown that autophagy was associated with the development of osteoarthritis (OA), the purpose of this research was to determine the exact role of autophagy in OA and investigate effective therapeutic drugs to inhibit the pathological progression of OA.MethodsIn this study, a cellular OA model was generated by stimulating SW1353 cells with IL-1β and a rabbit OA model was established by intra-articular injection of collagenase, followed by treatment with Torin 1 or 3-Methyladenine (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 50 publications
(53 reference statements)
0
53
0
Order By: Relevance
“…Torin 1 [84] and pp242 [85] have been reported to induce autophagy on account of their inhibition of MTOR activity. However, we found that Torin 1 and pp242 treatment did not enhance autophagy flux in HaCaT cells, although the increase in the conversion from LC3-I to LC3-II was observed in cells treated with them.…”
Section: Discussionmentioning
confidence: 99%
“…Torin 1 [84] and pp242 [85] have been reported to induce autophagy on account of their inhibition of MTOR activity. However, we found that Torin 1 and pp242 treatment did not enhance autophagy flux in HaCaT cells, although the increase in the conversion from LC3-I to LC3-II was observed in cells treated with them.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , autophagic inhibition stimulates apoptosis and an increase of matrix metalloproteinases in chondrocytes [5, 6]. Specifically, the relationship between compromised autophagy and the severity and progression of OA has been confirmed in many studies [7, 8]. Thus, in the progression of cartilage degeneration, finding a cause for the inhibition of chondrocyte autophagy during OA may become a potential strategy against this disease.…”
Section: Introductionmentioning
confidence: 99%
“…For inhibitor treatment in 2D and 3D cultures, 100 nM of rapamycin (Grabiner et al, 2014;Kang et al, 2013;Sarbassov et al, 2006), 250 nM of Torin1 (Cheng et al, 2016;Grabiner et al, 2014;Kang et al, 2013;Thoreen et al, 2012), 10 μM of PF47068671 (Pearce et al, 2010;Schipany et al, 2015;Zhang et al, 2015), 1 μM of MK2206 (Devery et al, 2015;Shen et al, 2015;Sung et al, 2016) and 1 μM of AZD6244 (Devery et al, 2015;Ewald et al, 2015) were employed as these concentrations have been most frequently used in cell-based assays and have a complete effect on their respective targets [ phospho-protein analysis in western blots (see Fig. 4 and western blots in the supporting figures)].…”
Section: Inhibitor Treatmentmentioning
confidence: 99%